QR Code Task Logger for Special Need Student on Continuous Achievement Monitoring - Mohd Azmey, Amirul Izzad; Mohamed Ali, Riyaz Ahmaz (Evolution in Electrical and Electronic Engineering, 2022)
Children with a Special Educational Needs (SEN) is a condition where this special child faces learning difficulties in the form of disorders and disabilities. Some of the most common learning disorders among these special children are Dyslexia, Dyscalculia and Dyspraxia. Not to forget that there are also children who have medical disorders such as Attention Deficit Hyperactivity Disorder (ADHD) and the most common disorder is Autism which will face learning disruptions as well. The goal of this study is to provide a learning aid to the teacher or instructor in order to monitor the progress and also the improvement of the special educational needs (SEN) students. With the help of this project, teachers may monitor and observe their SEN students and record all their progress instead of depending on observation only individually. For this project, the ESP32 Camera was used as a medium to scan QR codes that are encoded with the SEN students’ data that later will be stored in Microsoft Excel on a cloud server. The final result of this learning aid has demonstrated that it is possible to use this project in order to aid the workload of teachers and also can be quantitative evidence of the SEN students progression in the study.